2023
DOI: 10.3329/bjms.v22i2.65007
|View full text |Cite
|
Sign up to set email alerts
|

A predictive hypertension model for patients with dyslipidemia and type 2 diabetes mellitus: a robust hybrid methodology

Abstract: Background:Hypertension is a public health problem used to describe high blood pressure where the blood vessels are persistently increased in force. According to WHO, hypertension has been reported in one in four men and one in five women. Worldwide, hypertension is a common health problem that affects 20-30% of the adult population and more than 5-8% of pregnancies, and it is frequently curable when detected and treated early enough. Objective: This paper aims to validate the factor associatedwith hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…37,38 Burden of stroke is a soaring epidemic 39,40,41 , this study will give significant proof about the ideal risk factor of stroke, just as the duration of hypertension and diabetes denoted a standard protocol that depicts the ideal degree of acute stroke just as its viability and wellbeing. 42 Limitation of the study:…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Burden of stroke is a soaring epidemic 39,40,41 , this study will give significant proof about the ideal risk factor of stroke, just as the duration of hypertension and diabetes denoted a standard protocol that depicts the ideal degree of acute stroke just as its viability and wellbeing. 42 Limitation of the study:…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, our research demonstrated significant differences in health literacy scores between different groups, with health literacy strongly correlated to BP control status . 20,21 The Vietnamese government has introduced initiatives and policies aimed at enhancing awareness, healthcare capabilities, and management systems. 22 Insufficient knowledge about hypertension significantly contributes to the disregard of high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…23 Our study found a significant association between health literacy, self-care behavior, and blood pressure control, which is consistent with previous research. 8,21,24,25 Low health literacy levels can hinder patient participation in educational interventions, resulting in missed benefits and delays in adopting timely self-care behaviors. 26 Implementing a structured intervention to identify patients with low health literacy and provide hypertension self-care training can improve blood pressure control in the hypertensive population.…”
Section: Discussionmentioning
confidence: 99%